PENERAPAN NILAI-NILAI KEARIFAN LOKAL DALAM KEPEMIMPINAN CAMAT DI KANTOR KECAMATAN TAMALANREA KOTA MAKASSAR - Andi Wahyudi; Parakkasi Tjaija; Burhanuddin Burhanuddin (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
The purpose of this research is to determine the implementation of the values of local wisdom in the head of subdistrict leadership at the Subdistrict Office of Tamalanrea Makassar City. The approach is used a qualitative research. The data is obtained through direct observation in the field, in depth interviews with informants and document analysis. The research results are presented descriptively. The results show the implementation of the values of local wisdom in the head of sub district leadership at the Subdistrict Office Tamalanrea is not good enough. It is characterized by a lack of in the head of sub district attention the most value on local knowledge. The head of sub district leadership should be based on the implementation of the values of local wisdom as a manifestation of the identity of the government apparatus in favor of the society. Keywords: leadership, the values of local wisdom Penelitian ini bertujuan untuk mengetahui sejauh mana penerapan nilai-nilai kearifan lokal dalam kepemimpinan camat di Kantor Kecamatan Tamalanrea Kota Makassar. Pendekatan penelitian yang digunakan adalah kualitatif. Data diperoleh melalui pengamatan langsung di lapangan, wawancara secara mendalam dengan informan, serta analisis dokumen. Hasil penelitian dipaparkan secara deskriptif. Hasil penelitian menunjukkan penerapan nilai-nilai kearifan lokal dalam kepemimpinan camat di Kantor Kecamatan Tamalanrea belum cukup baik. Hal ini ditandai dengan kurangnya perhatian camat pada sebagian nilai pada kearifan lokal. Kepemimpinan camat haruslah berbasiskan pada pelaksanaan nilai-nilai kearifan lokal sebagai wujud identitas aparatur pemerintah yang berpihak pada masyarakat. Kata kunci: kepemimpinan, nilai-nilai kearifan lokal